INTERPRETASI SYAIKH AL-SHAWI TERHADAP AYAT-AYAT AL-HIDAYAH (STUDI SEMANTIK AYAT-AYAT AL-HIDAYAH) - Hidayatullah, Muh Gufron; Huda, Syamsul (An-Nisa': Jurnal Kajian Perempuan dan Keislaman, 2021)
Trem  Al-Hidayah  memiliki multi interpretasi yang berhubungan dengan jalan kehidupan (Sabil al-Hayat). Setiap insan diseru untuk menjalankan kehidupannya setakar dengan tolok ukur aturan Allah SWT (hududullah). Ia juga di haruskan untuk selalu mengikuti aturan individu, berkeluarga dan bermasyarakat (ijtimaiyyah). Bertolak dari itu semua, memahami petunjuk tuhan (al-Hidayah mina Allah) merupakan kebutuhan manusia yang subtansial. Agar didalam menjalankan kehidupannya baik yang sifatnya horizontal (hamblum minannas) atau vertikal (hamblum minallah) sesuai dengan Iradtullah. Eksplorasi ini bermaksud untuk memahami bagaimana syaikh al-Shawi dalam menafsirkan ayat-ayat al-Hidayah dalam kitabnya Tasfsir Hasiyah Shawi. Penelitian ini memakai metode kualitatif dengan model penelitian (al-Dirasah al-Maudluiyyah) yang tekanannya pada pendalaman pemahaman topic ayat-ayat al-Hidayah, kemudian mengunakan tehnik Content Analisys yaitu menganalisis hasil makna ayat-ayat al-Hidayah hasil tafsiran Syaikh al-Shawi dan analisis historis atau teori asbab al-Nuzul yaitu uaraian sejarah sebab-sebab turunnya ayat al-Qur’an. Hasil penelitian ini menunjukkan bahwa al-Hidayah bukanlah keberhasilan seseorang dalam menjalankan kehidupan, sebagaimana anggapan banyak orang akan tetapi al-Hidayah adalah petunjuk tuhan baik berupa al-Qur’an atau Sunnah beserta interpretasinya meskipun orang tersebut belum mengikuti petunjuk-Nya. The tram of Al-Hidayah is subject to multiple interpretations that intertwine with the pathway of life (Sabil al-Hayat). Every soul is commanded to conduct their life adhering to the etiquette arranged by Allah SWT (hududullah). One is also obligated to always follow the etiquette whether as an individual, in a family, and in a society (ijtimaiyyah). Following that, understanding the messages from God (al-Hidayah mina Allah) has then become a crucial necessity for one. In order to live a good life, be it in accordance to the Earth and everything within (hamblum minannas), or in accordance to God (hamblum minallah) entwined with Iradtullah. This exploration is meant to gain understanding on how Syaikh al-Shawi interpreted the passages of al-Hidayah in his book, Tasfsir Hasiyah Shawi. This research used the qualitative method with a research model (al-Dirasah al-Maudluiyyah) that emphasizes on deepening the understanding of the topics in al-Hidayah passages. Content analysis was then used to analyze the meaning of al-Hidayah passages according to Syaikh al-Shawi’s interpretation, and a historical analysis or the theory of asbab al-Nuzul, which is the chronological backstory to every passage of Al-Qur’an that has been passed down to the humankind. The result of this research showed that al-Hidayah is not about someone’s success in living their life as many have assumed, instead al-Hidayah is a direction from God in the form of both al-Qur’an and as-Sunnah along with its interpretations, even if one might have not yet followed His guidance.